Analgesic efficacy of articaine hydrochloride for velvet antler removal in red deer (Cervus elaphus) and analysis of drug residues in the harvested velvet antlers. Issue 5 (3rd September 2019) - Venkatachalam, D; Chambers, JP; Kongara, K; Singh, P
ABSTRACT: Aims: To investigate the analgesic efficacy of articaine hydrochloride for antler removal in red deer ( Cervus elaphus ) following S/C administration as a ring block, and to quantify the residue concentrations of articaine compared to lignocaine in the harvested antlers. Methods: Articaine hydrochloride (40 mg/mL) was administered to 10 male red deer as a ring block around the base of each antler at 1 mL/cm of pedicle circumference. Analgesia was evaluated by determining the response to a saw cut test every 1-minute, until no response was observed. Behaviour during and following removal of antlers was also recorded. Twenty commercially harvested velvet antlers were also collected following S/C administration of 2% lignocaine hydrochloride. A liquid chromatography-mass spectrometry (LC-MS) method for quantification of residues of articaine and lignocaine in velvet antlers was developed and validated. Results: In red deer administered 4% articaine hydrochloride as a ring block, the median interval to analgesia was 4 (min 3, max 5) minutes and no deer showed withdrawal responses during antler removal. There were no signs of toxicity or adverse effects up to 2 hours after administration. The sample preparation method developed for the LC-MS was simple and had acceptable extraction recoveries of articaine and lignocaine from the velvet antlers. The lower limits of quantification of lignocaine and articaine were 5 and 50 ng/g, respectively. Mean concentrations of articaine in antlers following ring block with 4% articaine hydrochloride were 1.50 (SD 1.09) mg/kg, and of lignocaine following ring block with 2% lignocaine hydrochloride were 0.66 (SD 0.71) mg/kg. Conclusions and clinical relevance: A ring block with 4% articaine hydrochloride at a dose of 1 mL/cm of pedicle circumference provided effective analgesia for velvet antler removal in red deer. The LC-MS method developed and validated to quantify articaine and lignocaine was simple and sensitive. Based on these results, articaine hydrochloride appears to be an effective alternative to lignocaine hydrochloride for velvet antler removal. However, further studies to evaluate the safety and residue concentrations of articaine and articainic acid are required before it can be recommended for use in deer.Abbreviations: DMA: 2, 6-dimethylaniline; LC-MS: Liquid chromatography-mass spectrometry; MEGX: Monoethylglycinexylidide; MRL: Maximum residue level